(untitled) (Biological Sciences - PJSIR, 2002)
Because of difficulties in producing more quantity and cheaper F1 hybrid seed, recently a possible alternative of using F2 1 hybrid seed is receiving more importance . Fou rteen F and F hybrids and their parents were compared for number of 2 bolls, seed cotton yield, li nt %, fibre length and fi bre uniformity ratio. F1 hybrids were superior to F2 hybrids and their parents for all the traits. However, some of F2 hybrids were also better than their high parents. The percent increase of some F2 hybrids against their high parent was 66.7% in n um ber of bolls per plant, 45.6% in seed cotton yield , 8.1 in lint %, 4.4% in fibre length and 4.8% in uniformity ratio. As expected, F2 hybrids have generally expressed about 50% of inbreeding depression; nevertheless, deviations to this expectation were also noted in particular characters and cross combinations. These deviations were probably attributable to abnormal segregation at meiosis due to higher ploidy level of cotton plant and deterioration of dominant factors on selfing. Significant performance of some F2 hybrids however suggested that parental choice and breeding objectives are very important when F, hybrids are considered for hybrid crop development.